PEMIKIRAN KEAGAMAAN MAHASISWA ISLAM PERGURUAN TINGGI UMUM NEGERI - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2012)
AbstractThis study focuses on how is religious thought of Muslim students in Public Colleges? Is it exclusive, inclusive, or liberal? And how far is the level of exclusivism, inclusivism or liberalism of their religious thoughts? The research findings showed that religious thoughts of Muslim students in Public Colleges tended to be exclusive and inclusive. The tendency of their religious thought was more strongly influenced by religious thoughts and activities at intra-campus organizations. The implication was religious guidance for Muslim students of Public Colleges, particularly those studying about Islamic Education, needed to consider the tendency of religious thought of Muslim students, especially from curriculum preparation aspects and religion learning models.AbstrakMasalah utama dalam penelitian ini adalah bagaimana pemikiran keagamaan mahasiswa Islam di Perguruan Tinggi Umum (PTU) Negeri, apakah eksklusif, inklusif, ataukah liberal? Dan seberapa jauh tingkat eksklusivisme, inklusivisme, atau liberalisme berpikir keagamaan mereka? Hasil penelitian menunjukkan bahwa pemikiran keagamaan mahasiswa Islam PTU Negeri cenderung eksklusif dan insklusif. Kecenderungan berpikir keagamaan mereka lebih kuat dipengaruhi oleh aktivitas dan pemikiran keagamaan di intra kampus. Implikasinya, pembinaan keagamaan bagi mahasiswa Islam PTU Negeri khususnya perkuliahan Pendidikan Agama Islam perlu mempertimbangkan kecenderungan pemikiran keagamaan mahasiswa Islam, terutama dari aspek penyusunan kurikulum dan model-model pembelajaran agama.